1990
DOI: 10.1128/jb.172.10.6135-6138.1990
|View full text |Cite
|
Sign up to set email alerts
|

groE genes affect SOS repair in Escherichia coli

Abstract: Repair of UV-irradiated bacteriophage in Escherichia coli by Weigle reactivation requires functional recA+ and umuD+C+ genes. When the cells were UV irradiated, the groE heat shock gene products, GroES and GroEL, were needed for at least 50% of the Weigle reactivation of the single-stranded DNA phage S13. Because of repression of the umuDC and recA genes, Weigle reactivation is normally blocked by the lexA3(Ind-) mutation (which creates a noncleavable LexA protein), but it was restored by a combination of a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Liu and Tessman have reported that groE mutations may have a greater effect on mutagenesis than they do on repair. The interactions between UmuC and GroEL and GroES, in addition to affecting the stability of UmuC, may alter its activity to promote mutagenic repair (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu and Tessman have reported that groE mutations may have a greater effect on mutagenesis than they do on repair. The interactions between UmuC and GroEL and GroES, in addition to affecting the stability of UmuC, may alter its activity to promote mutagenic repair (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…By analogy, the GroE proteins of E. coli may function in a similar fashion. Our previous work and the work of others have shown that the GroE proteins of E. coli are required for processes involved in DNA repair, i.e., UV mutagenesis (which is the specialized processing of UV-irradiated DNA that results in mutation introduction) (6) and Weigle reactivation (which is the repair of UV-irradiated bacteriophage) (17).…”
mentioning
confidence: 99%
“…Originally discovered as a gene whose mutations, groE, can lead to the failure of morphogenesis of bacteriophage X and other phages (6,13,44,46,52), subsequent genetic analysis produced mutants in one of two components, groEL (mopA) or groES (mopB) (47), which are defective in either DNA and RNA synthesis (50), SOS-induced mutagenesis and Weigle (UV) reactivation of UV-irradiated phage (7,26,33,43), protein export (31), proteolysis (45), septation (12), coupling of replication between F factor and the chromosome (36), or ability to grow at some or all temperatures (11,20). Further experiments implicated alterations in GroE levels or configuration in indirect suppression of a variety of mutations in other genes such as ssb (32,41), rpoH (30), dna (10,23), and various biosynthetic genes (48).…”
mentioning
confidence: 99%
“…Among these are the heat shock GroEL and GroES proteins, which are necessary for mutagenesis probably by stabilizing the UmuDC complex (8,22). Even though dinYis not involved in mutagenesis, it could be a member of the chaperonin family.…”
Section: Resultsmentioning
confidence: 99%